2016
DOI: 10.1111/jeb.12984
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection predicts brain structure in dragon lizards

Abstract: Phenotypic traits such as ornaments and armaments are generally shaped by sexual selection, which often favours larger and more elaborate males compared to females. But can sexual selection also influence the brain? Previous studies in vertebrates report contradictory results with no consistent pattern between variation in brain structure and the strength of sexual selection. We hypothesize that sexual selection will act in a consistent way on two vertebrate brain regions that directly regulate sexual behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 121 publications
2
18
1
Order By: Relevance
“…Sexual differences, most notably of secondary sexual characteristics, are a key aspect of within‐species variation impacting on anatomy, behavior, physiology, and life history (Chen, Stuart‐Fox, Hugall, & Symonds, 2012; Deepak et al 2016; Hoops et al, 2017; Littleford‐Colquhoun et al, 2019; McLean, Chan, Dickerson, Moussalli, & Stuart‐Fox, 2016; Stauber & Booth, 2003; Thompson & Withers, 2005; Wotherspoon & Burgin, 2011). Sex‐determination mechanisms in reptiles are incredibly diverse, exhibiting a rich evolutionary history of repeated independent transitions between sex‐determination modes (Alam, Sarre, Gleeson, Georges, & Ezaz, 2018; Gamble et al, 2015; Pokorna & Kratochvil, 2016; Sarre, Ezaz, & Georges, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual differences, most notably of secondary sexual characteristics, are a key aspect of within‐species variation impacting on anatomy, behavior, physiology, and life history (Chen, Stuart‐Fox, Hugall, & Symonds, 2012; Deepak et al 2016; Hoops et al, 2017; Littleford‐Colquhoun et al, 2019; McLean, Chan, Dickerson, Moussalli, & Stuart‐Fox, 2016; Stauber & Booth, 2003; Thompson & Withers, 2005; Wotherspoon & Burgin, 2011). Sex‐determination mechanisms in reptiles are incredibly diverse, exhibiting a rich evolutionary history of repeated independent transitions between sex‐determination modes (Alam, Sarre, Gleeson, Georges, & Ezaz, 2018; Gamble et al, 2015; Pokorna & Kratochvil, 2016; Sarre, Ezaz, & Georges, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern might indicate that males bite more forcefully and use biting to compete for access to females (Witten, 1994). Sexual dimorphism in head size (and possibly shape) may be common among agamid lizards (e.g., Hoops et al, 2017; Kuo, Lin, & Lin, 2009; Littleford‐Colquhoun et al, 2019; Stauber & Booth, 2003; Thompson & Withers, 2005; Wotherspoon & Burgin, 2011), and greater bite force associated with greater head size has been found in male eastern water dragons ( Intellagama lesueurii ; Baxter‐Gilbert & Whiting, 2019). Two species of spiny‐tailed agamid Uromastyx do not show obvious sexual differences in head dimensions or bite force but comparisons may be limited by sample size: n = 7:5 and 1:5 (Herrel, Castilla, Al‐Sulaiti, & Wessels, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we [Hoops et al, 2016] (and others [Powell and Leal, 2012]) used standard major axis regressions for this type of analysis, but recent evidence suggests that linear models are the preferred statistical method [Kilmer and Rodríguez, 2017;Smith, 2009;Hansen and Bartoszek, 2012]. Again, we centred and standardized the volumetric data for each brain subdivision prior to analysis.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…To date, the only study to look at the scaling of the major neural subdivisions across squamates found qualitative evidence for both concerted and mosaic brain evolution, but did not perform formal analyses [Platel, 1976]. There is evidence for mosaic brain evolution in lizards at the level of individual brain nuclei [ten Donkelaar, 1988;Lanuza and Halpern, 1997;Northcutt, 2013;Hoops et al, 2016], but none of these studies has examined evolution at the level of the major brain subdivisions. The only 2 studies Leal, 2012, 2014] to have quantitatively examined the evolution of the major brain subdivisions across multiple reptile species found concerted evolution with respect to body size but no other evidence of brain evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Brain size and structure evolve to generate adaptive behavior [Pravosudov and Clayton, 2002;Catania, 2012;Marzban et al, 2015;Carlson, 2016;Stöckl et al, 2016;Hoops et al, 2017], reflecting demands for cognitive ca-pability with respect to ecology as well as challenges associated with living in groups [Gronenberg and Liebig, 1999;Farris and Roberts, 2005;Dunbar and Shultz, 2007;O'Donnell et al, 2011;Herculano-Houzel, 2012;Muscedere and Traniello, 2012;Sheehan et al, 2019]. Although the association of brain structure and social evolution is unclear and controversial [Wehner et al, 2007;Riveros et al, 2012;Farris, 2015;Lihoreau et al, 2015;DeCasien et al, 2017], sociality has been considered a driver of brain size and organization in vertebrates and invertebrates.…”
Section: Introductionmentioning
confidence: 99%